Pasar Kecantikan dan Penindasan Wanita Di Cina - Inda Mustika Permata; Bima Jon Nanda (Andalas Journal of International Studies (AJIS), 2017)
This study examines about China beauty market associated with beauty perception in their society. The beautiful perception in China differs from time to time, most contradictory to the Mao era; beautiful women are women who did not do self-beautification, while post-Mao era, in line with the opening of the economy, beautiful women associated with white skin, young, and tall. To meet these criteria, women do beauty treatments and buy cosmetics so the demand for cosmetics becomes high. This behavior encourages the rise of cosmetic trading activities in China, so China has become one of the largest beauty market on global scale continues to grow. The rapid growth of the market in China cannot be separated from the Chinese beauty perception of women. Such perception ultimately oppresses women through demands to fulfill the beauty perception that exists in society. Later, beauty perception actually provides a great benefit for beauty companies in China.  Keywords: Beauty, Market, Women, China, Oppression